DIPLOMASI MARITIM INDONESIA DALAM ADMM-PLUS EXPERTS’ WORKING GROUPS ON MARITIME SECURITY TAHUN 2023 - Soplanit, Marsello Graito; Effendi, Irmawan (Department of International Relations Universitas Satya Negara Indonesia, 2024)
This article explains Indonesia's maritime diplomacy in the ADMM-Plus Experts' Working Group (EWG) on Maritime Security in 2023. This research aims to explore the significance of Indonesia's participation in this multilateral forum, with a focus on Indonesia's national interests. The research method used is qualitative with an internet-based research and document-based research approach and is supported by the concepts of maritime diplomacy and foreign policy. The research results show that Indonesia's participation in the ADMM-Plus EWG aim to strengthen Indonesia's identity as the world's maritime axis and promote international norms that support maritime peace and security in the Asia-Pacific region. This reflects the importance of Indonesia's maritime diplomacy as an instrument to achieve national and international strategic goals as well as Indonesia's contribution in the context of regional and global maritime security.